2016
DOI: 10.1586/14737175.2016.1130626
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of attention-deficit/hyperactivity disorder: an update

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder affecting children, adolescents, and adults. The prevalence is estimated at 5 to 7% of school-aged children and 2.5 to 5% of adults. The phenotype is complex and heterogeneous, presenting variable clinical features, developmental course, and outcome. The genetic susceptibility to ADHD is attributed to both common and rare variants from a broad range of genes related mainly to neurotransmission and neurodevelopment pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 108 publications
0
40
0
1
Order By: Relevance
“…Most patients with ADHD diagnosed within the study had other family members with ADHD or other neuropsychiatric disorders. This highlights the strong heredity of ADHD, as previously described . Presence of ADHD within the family should be requested by the diabetes team early in order to provide the family with special support.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Most patients with ADHD diagnosed within the study had other family members with ADHD or other neuropsychiatric disorders. This highlights the strong heredity of ADHD, as previously described . Presence of ADHD within the family should be requested by the diabetes team early in order to provide the family with special support.…”
Section: Discussionmentioning
confidence: 54%
“…This highlights the strong heredity of ADHD, as previously described. 24 Presence of ADHD within the family should be requested by the diabetes team early in order to provide the family with special support.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms should be present before 12 years of age, be clinically significant in ≥2 different environments and cause functional disabilities during ≥6 months. The heritability of ADHD is around 76%, suggesting a strong genetic role in ADHD aetiology (48). Thus parents of patients with ADHD are likely to carry the same condition.…”
Section: Executive Functioning Problems and Adhdmentioning
confidence: 99%
“…ADHD is a heterogeneous disorder that is possibly affected by a variety of genetic and environmental factors [3]. As with other causes, the genetic etiology of ADHD is still unclear, and many studies have reported that the genes related to the dopaminergic, serotonergic, and noradrenergic pathways are significantly associated with ADHD [4,5,6,7]. Among these genes, the DRD4 and DAT1 gene VNTR polymorphisms of the dopaminergic pathway, HTR1B gene polymorphisms (rs6296 and rs6298) of the serotonergic pathway, and NET gene polymorphisms (rs2242446, rs28386840, and rs5569) of the noradrenergic pathway have shown a consistent association with ADHD in the various populations [8,9,10].…”
Section: Introductionmentioning
confidence: 99%